O ardil de eros: o desejo em Anne Carson - Rafael Zacca (O Que Nos Faz Pensar)
This article aims to investigate the concept of desire in the work of the Canadian writer Anne Carson, based mainly, but not only, on an analysis of the essay Eros the bittersweet. Even though the essay is devoted to the description of how poets of the Greek melic tradition fabled love and desire, with a prominent place for Sappho in this description, the hypothesis to be tried out here is that there is, within Carson, an attempt at a metaphysical, or at least relatively ahistorical description of desire, which serves as basis for the studying the erotic emotional event in her subsequent works. Finally, the article also proposes that desire, as conceived by Carson, can substantiate and compensate for Western politics and civilization, as well as the colonial concept of barbarism.